Vacancy clustering in pure metals: some first principle calculations of positron lifetimes and momentum distributions - Luna, Carla Romina (2013)
First results of a systematic study on the vacancy clustering process in Al, Cu, Mg and Nb are presented. To this aim first principle calculation of positron lifetimes and positronelectron momentum distributions were performed. We test the reliability of the computational scheme used by comparing some of the calculated results with experimental ones.